Engineering faculty attitudes to general chemistry courses in engineering curricula - Garip, Mehmet U.; Erdil, Erzat; Bilsel, Ayhan (Amer Chemical Soc, 2006)
A survey on the attitudes of engineering faculty to chemistry, physics, and mathematics was conducted with the aim of clarifying the attitudes of engineering faculty to chemistry courses in relation to engineering education or curricula and assessing their expectations. The results confirm that on the whole chemistry is perceived as having a legitimate place as a core course in engineering curricula with frequently appearing comments from faculty to make chemistry relevant to real-life problems and everyday applications.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: CHEMISTRY; MULTIDISCIPLINARY, EDUCATION; SCIENTIFIC DISCIPLINES, Engineering Education